CAUSES OF PSYCHOLOGICAL CRISES IN PRESCHOOL-AGED CHILDREN - Davronova Sevinch Alisherovna, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract:  Psychological crises in preschool-aged children can significantly impact their emotional well-being and developmental trajectory. This article investigates the primary causes contributing to such crises, including familial, social, and environmental factors. The study draws on existing psychological theories and empirical research to highlight how changes in family dynamics, exposure to stressors, developmental challenges, and inadequate emotional support can trigger psychological disturbances in children aged 3 to 6. Understanding these causes is crucial for early identification, prevention, and effective intervention to support healthy psychological development.